Influence of Polyphenol Levels on the Perception of Aroma in Vitis vinifera cv. Malbec wine - Goldner, Maria Cristina (2011)
The aim of this study was to explore the effect of two ranges of polyphenols naturally present in Malbec wine, high concentrations (4.5-7.2 g/L) and low (1.4-3.2 g/L), on the perception of aroma. Samples with a maximum ethanol level of 13.5% were taken from the fermentation tanks before the clarification and filtration process. A Quantitative Descriptive Analysis of wines was assessed by ten trained assessors, and HS-SPME-GC-MS and physicochemical analyses were performed. The intensities of fruity (P < 0.01), citrus (P < 0.01), strawberry (P < 0.05), cooked fruit (P < 0.01) and floral (P < 0.01) aromas decreased when the level of polyphenols increased. Neither volatile compounds nor physicochemical analyses were significant in the two groups of wines.